2005
DOI: 10.1002/cne.20584
|View full text |Cite
|
Sign up to set email alerts
|

State‐dependent hemispheric specialization in the songbird brain

Abstract: Lateralization of brain functions is a widespread phenomenon in vertebrates. With the well-known lateralization in the processing of human speech and the parallels that exist between birdsong and language, songbirds are interesting for addressing such questions. In the present study, we investigated the central processing of communicative and artificial sounds in starlings, in an integrative part of the song system: the HVC. Neuronal responses to acoustic stimuli were systematically recorded in both hemisphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…Bilateral asymmetry with either left-sided or right-sided dominance, or differential dual specialization, has been previously observed in songbirds in relation to both central and peripheral control of song production (49)(50)(51)(52). As far as song perception is concerned, increased neuronal responsiveness to behaviorally relevant song stimuli has been observed in the field L complex and HVC on the right side in starlings (53,54). Right hemispheric specialization is seen only in awake birds.…”
Section: Familiar Song Stimuli Show Selective Differential Topographymentioning
confidence: 82%
“…Bilateral asymmetry with either left-sided or right-sided dominance, or differential dual specialization, has been previously observed in songbirds in relation to both central and peripheral control of song production (49)(50)(51)(52). As far as song perception is concerned, increased neuronal responsiveness to behaviorally relevant song stimuli has been observed in the field L complex and HVC on the right side in starlings (53,54). Right hemispheric specialization is seen only in awake birds.…”
Section: Familiar Song Stimuli Show Selective Differential Topographymentioning
confidence: 82%
“…Likewise, it has been suggested that there is a functional division of the two hemispheres in songbirds. In starlings, song processing in the left hemisphere might be more focussed on individual recognition of birds far away, while the right hemisphere may be specialised for analysing long and complex song sequences that birds in close proximity sing45. Another hypothesis is that lateralisation improves dual-task performance (i.e., when two tasks are executed simultaneously; Refs.…”
Section: Discussionmentioning
confidence: 99%
“…The degree to which auditory tuning in the awake bird is selective to the BOS might, however, vary with developmental age and even with the species being studied. For example, HVC neurons in juvenile zebra finches show auditory related responses to both tutor song and the bird’s own song during waking states early in development (Nick and Konishi, 2005) and recordings from HVC in Bengalese finches, starlings and several species of sparrows reveal auditory responses that are selective to the BOS in the awake animal (Margoliash and Konishi, 1985; George et al, 2005; Nealen and Schmidt, 2006; Prather et al, 2008; Sakata and Brainard, 2008; Prather et al, 2009). …”
Section: Auditory Responses In Nif and Hvcmentioning
confidence: 99%